Repositioning English Learners' Funds of Knowledge for Scientific Practices. Issue 3 (3rd July 2019) - Razfar, Aria; Nasir, Ambareen
Abstract : For more than 3 decades, education researchers have called on teachers to use funds of knowledge (FoK) as a way of creating more culturally relevant, responsive, and sustaining pedagogies. This is particularly important in the domains of science, technology, engineering, and mathematics (STEM) education, specifically mathematics and science. FoK research in this area has addressed how teachers have made connections to STEM, planned curriculum, and the challenges of integrating funds in STEM education. There remains a dearth of research on the process of gathering, selecting, planning, and implementing science-funds in particular. In this article, we conceptualize how FoK research can move toward more dynamic and hybrid forms of teaching and learning through positioning theory. Positioning theory provides a valuable framework for how teachers can gather, select, plan, and implement English learners' science-funds to teach the science standards by repositioning the role of language, nonschool funds, and interaction in the classroom.